A Study on Assessment of Health Related Quality of Life in COPD and Asthma Patients in a Tertiary Care Teaching Hospital - Malpani, Ashok Kumar; Waggi, Manjunath; Mukunda, Medari Santhekudlur; Jampa, Kiran; Sindhuri, Mayakuntla (Indian Journal of Pharmacy Practice)
Aim: The aim of this study was to evaluate the association between health-related quality of life (HRQL) and disease severity using both disease specific and generic specific questionnaires and lung function measures. Methods: A survey was performed in patients with COPD and Asthma in tertiary care teaching hospital. One hundred and twenty (120) subjects (92 men and 28 women, mean age 48.6 years) completed the generic HRQL questionnaire; the Short Form 36 (SF-36) and disease-specific HRQL questionnaire; the St George's Respiratory Questionnaire (SGRQ). The subjects were divided into four severity groups according to FEV1 percent of predicted normal using two clinical guidelines: GOLD and BTS. Results: From our study it was observed that the mean scores of SF-36 PCS is 40.46, p<0.0001 and MCS is 40.22, p<0.0001which showed an average HRQL and was significantly associated with COPD and Asthma. The COPD severity grades affected the SGRQ Total scores, varying from 67.8 to 22.9 (GOLD p<0.0001) and from 64.1 to 22.9 (BTS p<0.0001). The four stages of FVC% predicted had an impact on HRQL similar to the stages of FEV1% predicted outlined from GOLD and BTS. Strong negative correlation (-0.645, p<0.0001) was observed between SF-36 and SGRQ total scores, strong negative correlation (-0.847, p<0.0001) between SGRQ total scores and FEV1%/FVC% predicted in contrast with positive correlation (0.583, p<0.0001) with SF-36 and FEV1%/FVC% predicted. Conclusion: The results showed that HRQL in COPD deteriorates with disease severity and age. The results also showed that the level of HRQL of COPD and Asthma subjects deteriorate considerably with increase in the severity of disease and such deterioration showed linear relation to the decrease in the FEV1 % predicted normal values.
Keywords: COPD; HRQL; SF-36; SGRQ; PCS and MCS